2007
DOI: 10.1159/000105448
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonic Acid Can Significantly Prevent Early Insulin Resistance Induced by a High-Fat Diet

Abstract: Aim: To investigate whole-body metabolic disorder and hepatic glucose output (HGO) disturbance in rats with insulin resistance induced by a short-term high-fat diet, and the effect of arachidonic acid (AA). Methods: Twenty-four normal male Wistar rats (230–250 g) were randomly divided into 3 groups according to their weight and fed for 12 weeks: control group, n = 8, fed with standard chow diet; high-fat (HF) group, n = 8, fed with a high-fat diet; HF+AA group, n = 8, fed with a high-fat diet and administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…It is known that increased hepatic gluconeogenesis is induced by overexpression of PEPCK, a key gluconeogenic enzyme, and the catalytic subunit glucose-6-phosphatase, which is regulated by transcriptional and nontranscriptional mechanisms (46,47). PEPCK catalyzes one of the rate-limiting steps of gluconeogenesis, the reaction of oxaloacetic acid to phosphoenolpyruvate, contributing to increased hepatic glucose output and elevated blood glucose levels in the initial stages of type 2 diabetes characterized by insulin resistance (48). Expression of PEPCK is regulated by Akt and FOXO1.…”
Section: Mapkmentioning
confidence: 99%
“…It is known that increased hepatic gluconeogenesis is induced by overexpression of PEPCK, a key gluconeogenic enzyme, and the catalytic subunit glucose-6-phosphatase, which is regulated by transcriptional and nontranscriptional mechanisms (46,47). PEPCK catalyzes one of the rate-limiting steps of gluconeogenesis, the reaction of oxaloacetic acid to phosphoenolpyruvate, contributing to increased hepatic glucose output and elevated blood glucose levels in the initial stages of type 2 diabetes characterized by insulin resistance (48). Expression of PEPCK is regulated by Akt and FOXO1.…”
Section: Mapkmentioning
confidence: 99%
“…12,13 Hence, insulin resistance often is accompanied by increased circulating levels of insulin. [14][15][16] If this compensatory rise in insulin production is not maintained by the pancreas, causing insulin levels to drop, then type 2 diabetes ensues. [17][18][19] Questions Raised by Insulin Resistance…”
mentioning
confidence: 99%
“…Glucose over-production after longer durations was attributed to increased gluconeogenesis, but interestingly increased hepatic glycogen levels were also observed in rats after a 2-week high-fat diet [34, 35]. Longer high-fat diets also increased PEPCK expression [16, 36] and induced the citric acid cycle intermediates such as fumarate and citrate in liver of mice [37]. These changes were not observed in current study, but there are some similarity between current study and studies with longer high-fat diets.…”
Section: Discussionmentioning
confidence: 99%
“…It is also worth emphasizing that flux through specific pathways may not correlate closely with expression of the putative controlling enzymes [15]. For example, up-regulation of phospho enol pyruvate carboxykinase (PEPCK) expression after a 12-week high-fat diet [16] may not mean the same degree of PEPCK flux or not even glucose production. Burgess et al reported that substantial reduction of hepatic PEPCK contents caused only small changes in the flux through PEPCK [17].…”
Section: Introductionmentioning
confidence: 99%